2021
DOI: 10.1016/j.molp.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CHLOROPHYLLASE 1 protects young leaves from long-term photodamage by facilitating FtsH-mediated D1 degradation in photosystem II repair

Abstract: The proteolytic degradation of the photodamaged D1 core subunit during the photosystem II (PSII) repair cycle is well understood, but chlorophyll turnover during D1 degradation remains unclear. Here, we report that Arabidopsis thaliana CHLOROPHYLLASE 1 (CLH1) plays important roles in the PSII repair process. The abundance of CLH1 and CLH2 peaks in young leaves and is induced by high-light exposure. Seedlings of clh1 single and clh1-1/2-2 double mutants display increased photoinhibition after long-term high-lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 88 publications
1
46
0
Order By: Relevance
“…When photosystem (PS) damage occurs during stress conditions, PSII repair and Chl turnover subsequently occurs. A Chl turnover pathway is required for PSII repair and protection of young leaves from photodamage [7]. During leaf senescence or fruit maturation, Chl degradation is the major Chl metabolism direction.…”
Section: Introductionmentioning
confidence: 99%
“…When photosystem (PS) damage occurs during stress conditions, PSII repair and Chl turnover subsequently occurs. A Chl turnover pathway is required for PSII repair and protection of young leaves from photodamage [7]. During leaf senescence or fruit maturation, Chl degradation is the major Chl metabolism direction.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the amino acid sequences of CLHs are not very conserved across species and PPH is the core dephytylation enzyme during leaf senescence, but not during fruit ripening in tomato, it is possible that the function of CLHs varies in species or plant organs. Most recently, a report revealed additional information on CLHs [39,40]. It was found that Arabidopsis AtCLH1 was localized to the developing chloroplasts of young leaves but was located in the cytosol of mature leaves [39].…”
mentioning
confidence: 99%
“…Most recently, a report revealed additional information on CLHs [39,40]. It was found that Arabidopsis AtCLH1 was localized to the developing chloroplasts of young leaves but was located in the cytosol of mature leaves [39]. Leaves from CLH1-null mutant seedlings Most recently, a report revealed additional information on CLHs [39,40].…”
mentioning
confidence: 99%
See 2 more Smart Citations